Climate‐induced warming of lakes can be either amplified or suppressed by trends in water clarity. Issue 1 (24th October 2016) - Rose, Kevin C.; Winslow, Luke A.; Read, Jordan S.; Hansen, Gretchen J. A.
Abstract: Climate change is rapidly warming aquatic ecosystems including lakes and reservoirs. However, variability in lake characteristics can modulate how lakes respond to climate. Water clarity is especially important both because it influences the depth range over which heat is absorbed, and because it is changing in many lakes. Here, we show that simulated long‐term water clarity trends influence how both surface and bottom water temperatures of lakes and reservoirs respond to climate change. Clarity changes can either amplify or suppress climate‐induced warming, depending on lake depth and the direction of clarity change. Using a process‐based model to simulate 1894 north temperate lakes from 1979 to 2012, we show that a scenario of decreasing clarity at a conservative yet widely observed rate of 0.92% yr −1 warmed surface waters and cooled bottom waters at rates comparable in magnitude to climate‐induced warming. For lakes deeper than 6.5 m, decreasing clarity was sufficient to fully offset the effects of climate‐induced warming on median whole‐lake mean temperatures. Conversely, a scenario increasing clarity at the same rate cooled surface waters and warmed bottom waters relative to baseline warming rates. Furthermore, in 43% of lakes, increasing clarity more than doubled baseline bottom temperature warming rates. Long‐term empirical observations of water temperature in lakes with and without clarity trends support these simulation results. Together, these results demonstrate that water clarity trends may be as important as rising air temperatures in determining how waterbodies respond to climate change.